2013
DOI: 10.1371/journal.pone.0062189
|View full text |Cite
|
Sign up to set email alerts
|

The BTBR Mouse Model of Autism Spectrum Disorders Has Learning and Attentional Impairments and Alterations in Acetylcholine and Kynurenic Acid in Prefrontal Cortex

Abstract: Autism is a complex spectrum of disorders characterized by core behavioral deficits in social interaction, communication, repetitive stereotyped behaviors and restricted interests. Autism frequently presents with additional cognitive symptoms, including attentional deficits and intellectual disability. Preclinical models are important tools for studying the behavioral domains and biological underpinnings of autism, and potential treatment targets. The inbred BTBR T+tf/J (BTBR) mouse strain has been used as an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 66 publications
(70 reference statements)
6
85
0
Order By: Relevance
“…Recent studies demonstrated that low levels of ACh (McTighe et al, 2013) and reduction in striatal size (Ellegood et al, 2013b) accompany the aberrant behavior of this strain. Additionally, recent indirect evidence suggests E/I imbalance involvement in BTBR symptomology, as pharmacological modulation of glutamatergic synapses rescues these behaviors (Silverman et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies demonstrated that low levels of ACh (McTighe et al, 2013) and reduction in striatal size (Ellegood et al, 2013b) accompany the aberrant behavior of this strain. Additionally, recent indirect evidence suggests E/I imbalance involvement in BTBR symptomology, as pharmacological modulation of glutamatergic synapses rescues these behaviors (Silverman et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As an animal model, we used the BTBR T þ tf/J mouse strain, which is considered a reliable preclinical model for autism due to its distinct behavioral abnormalities resembling ASD symptoms including impaired social behavior, aberrant communication, increased repetitive behavior, and increased cognitive rigidity (reviewed in (Chadman and Guariglia, 2012)). Importantly, recent studies identified abnormally lower basal levels of brain ACh in BTBR mice compared with C57BL/6 mice (McTighe et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Only a response at the correct hole during the stimulus or limited hold was reinforced. Performance measures (correct, premature, and incorrect responses, and omissions) were reported as a percentage of the total number of trials (the sum of correct, premature, incorrect, and omitted trials) (McTighe et al, 2013;Scott and Taylor, 2014).…”
Section: -Choice Serial Reaction Time Test (5-csrtt)mentioning
confidence: 99%
“…When VAChT was overexpressed, mice displayed a profile of both impaired attention and impulsivity at shorter stimulus durations, with reduced accuracy and increased premature responding, respectively (Kolisnyk et al 2013a, b). The task has also been used to assess a model of autism, the inbred BTBR T+tf/J mouse, which also showed reduced levels of prefrontal acetylcholine (McTighe et al 2013). As in Kolisnyk et al (2013b), these mice showed impaired acquisition.…”
Section: Continuous Performance Testmentioning
confidence: 99%